Using material flow cost accounting (MFCA) to identify benefits of eco-efficiency and cleaner production in a paper and pulp manufacturing organization - Mishelle Doorasamy (Foundations of Management, 2016)
The aim of this study is to use material flow cost accounting (MFCA) to assess the level at which cleaner production (CP) can improve both environmental and economic performance of an organization. Higher energy and raw material prices are causing CP to grow in relevance and importance. The amount of waste to landfill is increasing steadily. Most companies are using inefficient processes and technologies that are obsolete resulting in higher production costs, which, in turn, affect their profitability and competitiveness. This study was a case study based on a paper manufacturing company using an exploratory qualitative and quantitative research methodology. The MFCA approach was used to assess the efficiency of the steam production process using coal-fired boilers. The results indicated that the process was inefficient resulting in significant negative environmental and economic impact. Environmental costs were hugely underestimated by management, as non-product output costs were not included as part of environmental costs calculated by company. Benefits and barriers to CP was also brought to the forefront at the conclusion of this research.
Keywords: 650; cleaner production; eco-efficiency; inefficient processes; environmental costs; nonproduct output costs